ANALISIS PENERAPAN AKUNTABILITAS, TRANSPARANSI DAN PARTISIPASI PENGELOLAAN ALOKASI DANA DESA DALAM PENCAPAIAN GOOD GOVERNANCE - Udzmah , Shinta Lailatul; Amalia, Firda Ayu; Wicaksono, Agung Prasetyo Nugroho (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
This research aims to analyze accountability, transparency and community participation in managing Village Fund Allocations in Candiwates Village, Prigen District, Pasuruan Regency in 2022, using a descriptive qualitative approach. with primary data sources and secondary data, using data collection methods through interviews and documentation. The results of the research show that the management of Village Fund Allocations in Candiwates Village is in accordance with the provisions stipulated in Domestic Regulation Number 20 of 2018. However, there are discrepancies in village administration because the recording of receipts and expenditures in the general cash book is carried out every 2-3 months for one report times. Transparency and participation in Candiwates Village is considered adequate from the planning to accountability stages and in accordance with the provisions of Domestic Regulation number 20 of 2018.